Short‐term efficacy and safety of early medical abortion in Japan: A multicenter prospective study - Yutaka Osuga; Kazuhiro Shirasu; Ruriko Tsushima; Ken Ishitani (Reproductive Medicine and Biology, 2023)
Abstract Purpose To evaluate the short‐term efficacy and safety of a combined mifepristone‐misoprostol regimen in individuals seeking medical abortion at up to 63 days of gestational age. Methods This open‐label, multicenter, prospective study evaluated the short‐term efficacy and safety of medical abortion, with the primary outcome being the abortion success rate 24 h after misoprostol administration. The participants received 200 mg of mifepristone orally and 800 μg of misoprostol buccally in the hospital/clinic 36–48 h later. Bleeding and lower abdominal pain, which are the main symptoms associated with medical abortion, were recorded. Results The abortion success rate was 93.3% (95% confidence interval [CI]: 87.3–97.1%) within 24 h of misoprostol administration, 63.3% (95% CI: 54.05–71.94%) within 4 h, and 90.0% (95% CI: 83.18–94.73%) within 8 h. The median time from misoprostol administration to a successful abortion was 3.93 h. Bleeding was most commonly observed 0–4 h prior to the confirmation of gestational sac (GS) expulsion. The most intense lower abdominal pain occurred 0–1 h before the confirmation of GS expulsion. Conclusion The combined regimen of mifepristone and buccal misoprostol for medical abortion showed short‐term efficacy and a favorable safety profile.